MRI-based high-precision irradiation in an orthotopic pancreatic tumor mouse model: A treatment planning study MRT-basierte Hochpräzisionsstrahlentherapie im orthotopen Pankreastumor-Mausmodell: Eine Bestrahlungsplanungsstudie - Dobiasch, S.; Kampfer, S.; Habermehl, D.; Duma, M. N.; Felix, K.; Strauss, A.; Schilling, D.; Wilkens, J. J.; Combs, S. E. (Strahlentherapie und Onkologie, 2018)
Background and purpose: Recently, imaging and high-precision irradiation devices for preclinical tumor models have been developed. Image-guided radiation therapy (IGRT) including innovative treatment planning techniques comparable to patient treatment can be achieved in a translational context. The study aims to evaluate magnetic resonance imaging/computed tomography (MRI/CT)-based treatment planning with different treatment techniques for high-precision radiation therapy (RT). Materials and methods: In an orthotopic pancreatic cancer model, MRI/CT-based radiation treatment planning was established. Three irradiation techniques (rotational, 3D multifield, stereotactic) were performed with the SARRP system (Small Animal Radiation Research Platform, Xstrahl Ltd., Camberley, UK). Dose distributions in gross tumor volume (GTV) and organs at risk (OAR) were analyzed for each treatment setting. Results: MRI with high soft tissue contrast improved imaging of GTV and OARs. Therefore MRI-based treatment planning enables precise contouring of GTV and OARs, thus, providing a perfect basis for an improved dose distribution and coverage of the GTV for all advanced radiation techniques. Conclusion: An MRI/CT-based treatment planning for high-precision IGRT using different techniques was established in an orthotopic pancreatic tumor model. Advanced radiation techniques allow considering perfect coverage of GTV and sparing of OARs in the preclinical setting and reflect clinical treatment plans of pancreatic cancer patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: High precision radiation therapy; Image-guided radiation; Pancreatic cancer; Preclinical tumor mouse model; Small animal radiation research platform